Advancements in understanding and treating psoriasis: a comprehensive review of pathophysiology, diagnosis, and therapeutic approaches - Sai Chakith M. R.; Sushma Pradeep; Manu Gangadhar; Chaithra Maheshwari N.; Shuaib Pasha; Shiva Prasad Kollur; Nagashree S.; Chandan Shivamallu; Satish Allur Mallanna (PeerJ)
Psoriasis is a chronic autoimmune disease affecting millions worldwide. This condition is characterized by scaly, red patches of skin that can be painful, itchy, and disfiguring. This non-contagious illness forms plaques and accelerates the dermal cell’s life cycle. This review provides a comprehensive overview of the current knowledge on psoriasis, covering its definition, prevalence, causes, pathogenesis, clinical features, diagnosis, and treatment options. The psychosocial impact of psoriasis on patients and their coping mechanisms is also explored. Biologic agents, which target specific cytokines involved in psoriasis pathogenesis, have revolutionized psoriasis treatment and have significantly improved patient outcomes. However, effective and safe treatments for moderate to severe psoriasis are still needed. Future research directions include the development of biomarkers for predicting disease severity and treatment response, investigating new therapeutic targets like the microbiome and epigenetics, and leveraging advancements in technology and genomics for deeper insights into psoriasis pathogenesis and treatment. This study summarizes the key aspects of psoriasis, including its epidemiology, pathophysiology, clinical traits, disease burden, and management. However, further research is needed to improve treatment outcomes and enhance the quality of life for patients affected by this complex condition.